2011
DOI: 10.3164/jcbn.10-145
|View full text |Cite
|
Sign up to set email alerts
|

Temperature-dependent free radical reaction in water

Abstract: Temperature-dependent free radical reactions were investigated using nitroxyl radicals as redox probes. Reactions of two types of nitroxyl radicals, TEMPOL (4-hydroxyl-2,2,6,6-tetramethylpiperidine-N-oxyl) and carbamoyl-PROXYL (3-carbamoyl-2,2,5,5-tetramethylpyrrolidine-N-oxyl), were tested in this paper. Heating a solution containing a nitroxyl radical and a reduced form of glutathione (GSH) caused temperature-dependent decay of electron paramagnetic resonance (EPR) signal of the nitroxyl radical. Heating a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 15 publications
1
12
0
Order By: Relevance
“…The oxoamonium cation form of TEMPOL then could react with GS • to make a stable non-paramagnetic complex and as a result TEMPOL was two-electron-reduced. (13) On the other hand, NBT can be directly reduced by O 2 •− to give blue formazan dye. Strong reductants, such as ascorbic acid, can also reduce NBT and give the blue formazan (data not shown).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The oxoamonium cation form of TEMPOL then could react with GS • to make a stable non-paramagnetic complex and as a result TEMPOL was two-electron-reduced. (13) On the other hand, NBT can be directly reduced by O 2 •− to give blue formazan dye. Strong reductants, such as ascorbic acid, can also reduce NBT and give the blue formazan (data not shown).…”
Section: Resultsmentioning
confidence: 99%
“…(13,14) Incubating a reaction mixture containing 4-hydroxyl-2,2,6,6-tetramethylpiperidine- N -oxyl (TEMPOL) and GSH at 44°C, the TEMPOL shows a steep reduction following a short time delay. This characteristic TEMPOL reduction was halted by adding superoxide dismutase (SOD) to the reaction mixture or bubbling N 2 gas through the reaction mixture.…”
Section: Introductionmentioning
confidence: 99%
“…Since DMPO-OH is a nitroxyl radical, the method may be disrupted by hydrogen donors, such as NAD(P)H, and/or some thiol compounds, such as GSH. (19,20) Applying other detection methods, such as luminescence probes, may make the method available for thiol compounds and other inapplicable cases.…”
Section: Resultsmentioning
confidence: 99%
“…TEMPOL, which is in the nitroxyl group (>N-O·), appears to be quickly converted into hydroxylamine (>N-OH) and a non-paramagnetic compound through one-electron reductions and other reactions that occur within biological systems. 26,27 In our study, we found there was a rapid decrease of the signal intensity of TEMPOL after the reduction of TEMPOL to hydroxylamine. We confirmed that the decay rate of TEMPOL follows pseudo-first-order kinetics, meaning that the initial phase of the semi-logarithmic plots of the signal intensity against time will give a straight line (R > 0.995).…”
Section: Discussionmentioning
confidence: 69%